Freedom from sinful thoughts - Arnold, Heinrich J. 1913-1982. (Secunderabad, OM Books., 2001)
Sensitive and compassionate, yet always pragmatic, Freedom from Sinful Thoughts offers insights into a crucial universal struggle. Drawing on the words of Jesus, and on years of experience as a pastoral counselor, J. Heinrich Arnold guides the reader from the throes of frustration, guilt, and self doubt to a life of single-minded freedom and joy.
The struggle -- Temptation -- Deliberate sin -- The will -- The power of suggestion -- Autosuggestion -- Fascination -- Suppression -- Faith -- Self-surrender -- Confession -- Prayer -- Detachment -- Repentance and rebirth -- Healing -- Purification -- The cross -- Living for the kingdom.
Keywords: Christian life; Thought and thinking -- Religious aspects -- Christianity; Temptation; Sin -- Christianity